Cost savings in hospital materials management: look-back versus look-ahead inventory policies. (2015) - Iannone, Raffaele; Lambiase, Alfredo; Miranda, Salvatore; Riemma, Stefano; Sarno, Debora
The hospital materials management process deals with the coordination of all activities related to materials ordering, holding, and administering. It is usually treated with a look-back approach, by which materials are 'pushed' into the hospital on the basis of demand forecasts, while high stock levels are distributed throughout the system to prevent stockouts. This study analyses the possibility of reducing stocks while assuring a high service level to patients, and proposes an integrated approach to the supply chain. Medical information is used to issue orders (look-ahead approach), in a 'pulled' flow of information from bed to hospital pharmacy warehouses. The two approaches are compared by means of a discrete event simulation in different scenarios: cost savings can range from 2% to 7%; the higher the demand variability, the greater the convenience; the savings are slightly influenced by variations in external stockouts and pharmacy ordering costs.